Measuring Frailty Using Claims Data for Pharmacoepidemiologic Studies of Mortality in Older Adults: Evidence and Recommendations - Kim, Dae Hyun (2014)
PURPOSE: Geriatric frailty is a common syndrome of older adults that is characterized by increased vulnerability to adverse health outcomes and influences treatment choice. Pharmacoepidemiologic studies in older adults that rely on administrative claims data are limited by confounding due to unmeasured frailty. A claim-based frailty score may be useful to minimize confounding by frailty in such databases. We provide an overview of definitions and measurement of frailty, evaluated the claim-based models of frailty in literature, and recommend ways to improve frailty adjustment in claims analysis. METHODS: We searched MEDLINE and EMBASE from inception to April 2014, without language restriction, to identify claim-based multivariable models that predicted frailty or its related outcome, disability. We critically appraised their approach, including population, predictor selection, outcome definition, and model performance. RESULTS: Of 152 reports, three models were identified. One model that predicted poor functional status using health care service claims in a representative sample of community-dwelling and institutionalized older adults showed an excellent discrimination (C statistic, 0.92). The other two models that predicted disability using either diagnosis codes or prescription claims alone in institutionalized or frail adults had limited generalizability and modest model performance. None of the models have been applied to reduce confounding bias in pharmacoepidemiologic studies of drug therapy. CONCLUSIONS: We found little research conducted on development and application of a claim-based frailty index for confounding adjustment in pharmacoepidemiologic studies in older adults. More research is needed to advance this innovative, potentially useful approach by incorporating the expertise from aging research.